Fault-Tolerance Distributed Control Plane for Software Defined Networks - Vasily N. Pashkov (Моделирование и анализ информационных систем, 2019)
The architecture of the high availability distributed control plane for SDN/OpenFlow networks are considered. High availability is achieved by redundancy of controller instances, active switch-controller communications, computing resources and tools for a controller instance failure and overloading detection and recovery. The proactive backup controller allocation algorithm which allows to minimize the time to repair in the case of a single controller instance failure is discussed. The algorithm for controller load-balancing allows dynamically reconfigure the control plane with a minimum number of switch control transfer operations to avoid controller instance overloading. The initial experimental results of the proposed algorithms for the HA distributed SDN control plane are described.